2014
DOI: 10.1007/s11103-014-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-directed downregulation of betaine aldehyde dehydrogenase 1 (OsBADH1) results in decreased stress tolerance and increased oxidative markers without affecting glycine betaine biosynthesis in rice (Oryza sativa)

Abstract: As an important osmoprotectant, glycine betaine (GB) plays an essential role in resistance to abiotic stress in a variety of organisms, including rice (Oryza sativa L.). However, GB content is too low to be detectable in rice, although rice genome possesses several orthologs coding for betaine aldehyde dehydrogenase (BADH) involved in plant GB biosynthesis. Rice BADH1 (OsBADH1) has been shown to be targeted to peroxisome and its overexpression resulted in increased GB biosynthesis and tolerance to abiotic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Yang et al [56] reported that overexpressing aldehyde dehydrogenase gene confers drought and salt tolerance in tobacco. Consistent with this finding, overexpressing aldehyde dehydrogenase 7 improved the drought tolerance in Arabidopsis [43], and increased aldehyde dehydrogenase activity is linked with improved stress tolerance in rice [57]. The results of the present study are in agreement with these previous reports, suggesting that aldehyde dehydrogenase has an essential role in drought stress tolerance and recovery in soybean.…”
Section: Peroxidase and Aldehyde Dehydrogenase Are Critical For Post-supporting
confidence: 93%
“…Yang et al [56] reported that overexpressing aldehyde dehydrogenase gene confers drought and salt tolerance in tobacco. Consistent with this finding, overexpressing aldehyde dehydrogenase 7 improved the drought tolerance in Arabidopsis [43], and increased aldehyde dehydrogenase activity is linked with improved stress tolerance in rice [57]. The results of the present study are in agreement with these previous reports, suggesting that aldehyde dehydrogenase has an essential role in drought stress tolerance and recovery in soybean.…”
Section: Peroxidase and Aldehyde Dehydrogenase Are Critical For Post-supporting
confidence: 93%
“…BADH converts betaine aldehyde to glycine betaine, which mediates osmotic homeostasis, and has positive effects on plant adaptation to drought stress [164]. RNAi-directed downregulation of OsBADH1 resulted in a decrease of stress tolerance and an increase of oxidative stress [165], implying its important role in plant drought tolerance.…”
Section: Osmotic Regulationmentioning
confidence: 99%
“…The up-regulation of catalase isozyme B (U301, D0D9C4) by bentazon is beneficial in protecting cells from the toxic effects of hydrogen peroxide; catalase is a typical antioxidant and is strongly up-regulated by other stresses [32]. ALDH (aldehyde dehydrogenase) (U285, Q9FRX7) and STR (strictosidine synthase) (U904, Q75LL5) are also biomarkers of biotic stress [33][34][35]. ALDH induction has been observed in a variety of plant species exposed to heat, dehydration, salinity, oxidants, ultraviolet radiation, pesticides, or metals [36].…”
Section: Bentazon Induced Antioxidant Expression and Caused Biotic Stmentioning
confidence: 99%